2017
DOI: 10.1021/acs.jchemed.7b00438
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost Time-Resolved Spectrometer for the Study of Ruby Emission

Abstract: A low-cost time-resolved emission spectrometer optimized for ruby emission is presented. The use of a Class II diode laser module as the excitation source reduces costs and hazards. The design presented here can facilitate the inclusion of time-resolved emission spectroscopy with laser excitation sources in the undergraduate laboratory curriculum. The ruby decay data show evidence of radiation trapping, an interesting optical phenomenon discussed in the research literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This miniature detector has opened the door for convenient photon counting methodologies to be explored in teaching laboratories. Although several experiments suitable for undergraduate students have been described in the education literature using the SiPM, and its simpler precursor, the avalanche photodiode, these techniques are not rigorously considered photon counting as they are operated in analog mode rather than true Geiger mode, allowing detection of ultra low light levels from samples. These previous reports include a recent description of the construction of a rudimentary SiPM-based photon counting device, along with a laboratory experiment involving the measurement of the phosphorescent lifetime of a ruthenium polypyridyl complex .…”
Section: Introductionmentioning
confidence: 99%
“…This miniature detector has opened the door for convenient photon counting methodologies to be explored in teaching laboratories. Although several experiments suitable for undergraduate students have been described in the education literature using the SiPM, and its simpler precursor, the avalanche photodiode, these techniques are not rigorously considered photon counting as they are operated in analog mode rather than true Geiger mode, allowing detection of ultra low light levels from samples. These previous reports include a recent description of the construction of a rudimentary SiPM-based photon counting device, along with a laboratory experiment involving the measurement of the phosphorescent lifetime of a ruthenium polypyridyl complex .…”
Section: Introductionmentioning
confidence: 99%
“…Lasers are useful because of their high light intensities, narrow bandwidths, and the coherent nature of laser light. Furthermore, several inexpensive lasers are widely available, and therefore, lasers are an attractive light source for several spectroscopy and kinetics undergraduate chemistry laboratory experiments. In particular, the newly established chemistry course at Saint Mary’s University, Instrumental Analysis for Materials Chemistry, has a strong focus on advanced spectroscopy, with most laboratories utilizing a laser, including a recently published laboratory employing a polarimeter to measure scattering .…”
Section: Introductionmentioning
confidence: 99%
“…Especially, ingenuity is required to implement this as part of a laboratory class since this type of measurement typically requires a high-voltage source (200–1000 V) for photomultiplier tube, an oscilloscope, and/or a laser system generating pulsed light. Thus, several measurement systems with such ingenuity have been reported in this Journal ; nonetheless, no system has been reported that satisfies the following four practical points: (1) it must respond to a wide range of time scales from nanoseconds to milliseconds; (2) it must be small and operable by a few students; (3) it must be inexpensive as an instrument for use in a laboratory class; and (4) the system configuration must be easily understood by students.…”
Section: Introductionmentioning
confidence: 99%